PERSEPSI MASYARAKAT KELURAHAN JAYENGAN TERHADAP IKLAN POLITIK MELALUI MEDIA BALIHO PADA PILKADA SURAKARTA 2024 - Oryza Putri; Herning Suryo S (Solidaritas, 2025)
In the lead-up to the election, public spaces across the city are often filled with large political billboards. Nearly every intersection, market, and other strategic areas feature candidates' faces with concise and striking campaign slogans. This study aims to understand the perceptions of the residents of Jayengan Village towards political advertising through billboards in the context of the 2024 Surakarta Regional Election. The background to this research is based on the fact that, in the lead-up to the election, residents often complain about the large number of political billboards that fill the city, disrupting the aesthetics and comfort of the environment. Furthermore, political billboards are often considered less essential because they take up a lot of space in urban areas. The installation of billboards by candidates in irregular locations requires proper management to prevent urban disorder. The method used is a qualitative approach with data collection techniques through field observations and in-depth interviews with six informants, including four residents and two campaign teams from each candidate. The results of this study indicate that public perception of political billboards is influenced by internal factors such as personal experience, political attitudes, and background information, as well as external factors such as visual design, placement location, and the symbols used on the billboards. Most informants considered billboards merely a means of candidate identification, not a primary medium influencing political choices. Keywords: Perception, Political Communication, Billboards, Surakarta Regional Election, Campaign Strategy.